Analysis of factors related to the performance of implementing nurses at Permata Bunda Medan Hospital - Utikasari, Rizkia; Sipayung, Rosetty Rita (Gema Wiralodra, 2024)
This study aimed to determine the factors associated with the performance of implementing nurses. This type of research is quantitative research with a cross-sectional approach. The population in this study were the nurses who worked in the inpatient room of Permata Bunda Hospital in Medan. The sample is determined by total sampling which amounted to 140 people. Data collection was using a questionnaire. The analysis methods are univariate, bivariate, and multivariate and are presented in narrative and table form. The univariate analysis revealed key demographic trends among respondents, indicating a predominance of female participants with undergraduate bachelor's degrees, aged 21-30 years, and having an average work experience of 2-5 years. Additionally, factors such as good supervision, training, wage system, environment, and facilities were generally reported positively by the majority of respondents. Bivariate analysis demonstrated significant correlations with nurse performance between supervisory, training, wage system, environmental, and facility factors. The multivariate analysis identified facility factors as the dominant influencer on nurse performance, with an Exp (B) value of 8.357. The implication of this research is the need for improvement in supervision, training, payroll system, work environment, and facilities to support the performance of implementing nurses at Permata Bunda Medan Hospital.